Positive and Negative Experiences of Living in COVID-19 Pandemic: Analysis of Italian Adolescents’ Narratives - Fioretti, Chiara; Palladino, Benedetta Emanuela; Nocentini, Annalaura; Menesini, Ersilia (Frontiers in Psychology, 2020)
Introduction. Despite a growing interest in the field, scarce narrative studies have delved into adolescents’ psychological experiences related to global emergencies caused by infective diseases. The present study aims to investigate adolescents’ narratives on positive and negative experiences related to COVID-19. Methods. 2758 Italian adolescents (Females= 74.8%; mean age = 16.64, SD=1.43) completed two narrative tasks on their most negative and positive experiences during the COVID-19 emergency. Data were analyzed by modeling an analysis of emergent themes. Results. “Staying home as a limitation of autonomy”, “School as an educational, not relational environment”, the impact of a “new life routine” and experiencing “anguish and loss” are the four emergent themes for negative experiences. As for positive experiences, the four themes were “Being part of an extraordinary experience”, “Discovering oneself”, “Re-discovering family” and “Sharing life at a distance”. Conclusions. Authors discuss the impact of COVID-19 on adolescents’ developmental tasks, such as identity processes and autonomy acquisition.